Intercultural Approach to Language Teaching - Ranabhat, Bijaya Kumar (Marsyangdi Journal, 2024)
The intercultural approach to language teaching aims to develop intercultural communicative competence on the part of the learners. This study ’Intercultural Approach to Language Teaching’ primarily aims to explore the significance of the intercultural approach to language teaching. Additionally, it discusses the various components of intercultural communicative competence. Similarly, it offers some insights on the role of teachers and students in intercultural approach to language teaching, and strategies or modes of assessing the learners’ intercultural communicative competence. The study reveals that because of the unrealistic, utopian, constrained, and decontextualized nature of communicative competence, learners need to develop intercultural communicative competence to learn the language effectively in cross-cultural settings. It was also found that closed and open-ended questions, individual and interactive activities, dialogues, interviews, presentations, demonstrations, poster sessions, simulations, role plays, self-evaluation reports, portfolios, and observation checklists are the major activities that help the teachers to assess their learners’ intercultural communicative competence and to enable learners to preserve, exchange and respect each other’s cultures in cross-cultural settings.